An Evaluation of the Comprehensive Development Capacity —— Energy-based Cities in China. (December 2016) - Zhang, Wenqiang; Zhao, Fang; Wang, Yetang
Abstract: To quantify the comprehensive development capacity of energy-based cities, the evaluation index system is established. Based on this index system, principal component analysis is used to evaluate the comprehensive development capacity. The past development of the energy-based cities seriously depends on energy exploitation and consumption, and the environmental protection is often ignored. As a result, these cities experienced serious environmental pollution and ecological destruction. With the superiority of the eastern and central region cities to the western, comprehensive development capacity varies from one region to another. High development capability and high vulnerability coexist among the energy-based cities in China. The industrial structure is single, and the secondary industry remains dominant.